Ms № 1467 Of Arabic Script Manuscripts Collection of the Matenadaran as a Newfound Example of the "Collection of Verse Dictionaries" - Ani Avetisyan (Banber Arevelagitut'yan Instituti)
The present article touches upon a series of Ottoman Turkish manuscripts from the Matenadaran's Arabic script manuscripts collection, an example of a unique collection in Ottoman Turkish manuscripts known as the "Collection of Verse Dictionaries" MS No. 1467, in order to provide the first detailed study. These collections were compiled at the religious-educational institutions called tekke or dergāh, and the medrese. They were compiled as language textbooks, in order to provide easy learning of languages (Arabic, Persian, Ottoman Turkish) through the simultaneous use of several verse dictionaries and to be engaged in the process of learning languages by heart. The unique copy of the Matenadaran’s "Collection of Verse Dictionaries" includes 3 complete copies of bilingual (Arabic-Ottoman Turkish) and trilingual (Arabic-Persian-Ottoman Turkish) verse dictionaries of the 14th-15th, 17th and 19th-century writers: copies of Ferişteoġlu ʽAbdullaṭīf ibn Melek’s (proper name was ʽAbdullaīf ʽİzzeddīn et-Tirevī) "Luġat-i Ferişteoġlū" and Bosnalı Ebū̕ l-Fāżl Muḥammed (Meḥmed) ibn Aḥmed er-Rūmī's "Ṣubha-i Ṣıbyān" Arabic-Ottoman Turkish and also complete copy of Adanalı Ḫōca Meḥmed Ḥayret's (propar name was Meḥmed Behāeddīn Ḥayret) "Tuḥfe-i Zībā" (known with another titles as "Tuḥḥfe-i Dürrī" or "Tuḥfe-i Ḥayret" or "Tuḥfe-i Se Zebān") Arabic-Persian-Ottoman Turkish verse dictionaries. The article presents in detail the works included in the collection. At the same time, it has touched upon the methodology of writing verse dictionaries in classical Turkish literature, their structural features, the significance and role of dictionaries in Turkish society, religion, literature and education. The purposes of writing verse dictionaries in all cases were to teach languages, to develop and spread literary speech, and to practice in prosody (especially in ʽArūż meter). The comprehensive presentation of the collection is even sufficient for it to become a part of the manuscripts of the four collections, already known in foreign collections as the "Collection of Verse Dictionaries", in order to become a source of new research opportunities for local and foreign specialists.